From hesitation to integration: A UTAUT model analysis of ChatGPT adoption in Moroccan universities - Ali, Bennagem Touati; Abdellah, Hadj-Ali; Hicham, Ouzif; Ouidad, Benlamrabet; Mohamed, Es-Sanoun (Edelweiss Applied Science and Technology, 2025)
This study explores the determinants of ChatGPT adoption by Moroccan university teachers, applying the UTAUT model. The results show that facilitating conditions have a significant and positive effect on the intention to use, underlining the importance of resources and institutional support in fostering the adoption of this technology. Social influence also exerts a significant positive impact, indicating that the opinions of colleagues and superiors play an important role in teachers’ decisions. Effort expectancy, on the other hand, shows a negative effect, suggesting that teachers perceive some difficulty in using ChatGPT. Finally, perceived usefulness shows no significant effect, suggesting that teachers do not yet fully perceive the benefits of the tool for their teaching practices. These results have important implications for institutions, which should strengthen the technical infrastructure and provide better pedagogical support to encourage the adoption of educational technologies such as ChatGPT in Moroccan universities.